Association between food insecurity and probable sarcopenia: Data from the 2011–2014 National Health and nutrition examination survey. Issue 9 (September 2022) - Lynch, David H.; Petersen, Curtis L.; Van Dongen, Matthew J.; Spangler, Hillary B.; Berkowitz, Seth A.; Batsis, John A.
Summary: Background: Aging alters biological processes resulting in body fat redistribution, loss of lean muscle mass, and reduced muscle strength, termed sarcopenia. Nutrition is an important modifiable risk factor in the development of sarcopenia. Food insecurity refers to limited or uncertain access to enough food for an active, healthy life, and is prevalent among older adults. The objective of this study was to examine the relationship between food insecurity and probable sarcopenia in older adults. Methods: We examined 3632 adults ≥60 years old from the 2011–2014 National Health and Nutrition Examination Surveys (NHANES). For our analysis food insecurity was identified using the Food Security Survey Module (FSSM). The primary outcome was based on the Sarcopenia Definitions and Outcomes consortium (SDOC) definition. Secondary outcomes were based on three other different grip strength cut-offs as there is debate within the field as to the optimal definition of sarcopenia. Consistent with the revised European consensus on the definition and diagnosis of Sarcopenia (EWGSOP2) recommendations, we used the term probable sarcopenia throughout this text as definitions were based on muscle strength alone and did not include an evaluation of muscle quality. Sensitivity analyses were performed using the standard four category definition of food security. We used logistic regression to examine the association between food insecurity and sarcopenia. Results: Using the Sarcopenia Definitions and Outcomes Consortium definition, 24.7% were classified as having probable sarcopenia (low grip strength); 5.5% had food insecurity and food insecurity was associated with probable sarcopenia (OR 1.51, 95%CI 1.03–2.22). Using three other definitions of probable sarcopenia, food insecurity was significantly associated with probable sarcopenia using the Foundation for the National Institute of Health definition using grip strength alone (OR 1.71, 95%CI 1.08–2.71), but food insecurity was not associated with food insecurity using definitions related to grip strength/BMI (OR 1.16, 95%CI 0.76–1.78) or grip strength/weight (OR 1.14, 95%CI 0.85–1.54). Conclusions: In this nationally representative cohort study, individuals classified as having food insecurity were more likely to have probable sarcopenia (low grip strength) compared to those with full food security. Future studies should examine whether food insecurity interventions may reduce probable sarcopenia and associated adverse outcomes.